Arabic ID-DGBL :an instructional design (ID) model for e-arabic teaching and learning - Sahrir, Muhammad Sabri; Zainuddin, Nurkhamimi; Wan Abdullah, Wan Najmuddin (2012)
Educational games have been among teaching and learning aids in many disciplines of knowledge. The games are varying between traditional non-computer games computer or digital games. Every mode of educational games has its own history of existing, design and development frameworks, related learning theories, evaluation frameworks, development tools, genres of different games, findings and implications on certain fields, learners, theories, and so on.